2022
DOI: 10.1093/cercor/bhac282
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced left superior parietal activation during successful speech production in patients with left dorsal striatal damage and error-prone neurotypical participants

Abstract: Functional imaging studies of neurotypical adults report activation in the left putamen during speech production. The current study asked how stroke survivors with left putamen damage are able to produce correct spoken responses during a range of speech production tasks. Using functional magnetic resonance imaging, activation during correct speech production responses was assessed in 5 stroke patients with circumscribed left dorsal striatal lesions, 66 stroke patient controls who did not have focal left dorsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…However, it is also known as the language area (Brownsett & Wise, 2009). In a recent study, Geva et al (2022) tried to investigate patients with damaged putamen to observe which brain would contribute to speech production; they used tasks that were needed over speech production and semantic decision tasks. They found that the left superior parietal was activated during tasks that needed more speech production.…”
Section: Left Superior Parietal Lobulementioning
confidence: 99%
“…However, it is also known as the language area (Brownsett & Wise, 2009). In a recent study, Geva et al (2022) tried to investigate patients with damaged putamen to observe which brain would contribute to speech production; they used tasks that were needed over speech production and semantic decision tasks. They found that the left superior parietal was activated during tasks that needed more speech production.…”
Section: Left Superior Parietal Lobulementioning
confidence: 99%